Impact of Helicobacter pylori and/or Helicobacter pylori‐related metabolic syndrome on gastroesophageal reflux disease‐ Barrett's esophagus‐ esophageal adenocarcinoma sequence. Issue 6 (12th September 2018) - Doulberis, Michael; Kountouras, Jannis; Polyzos, Stergios A.; Tzivras, Dimitri; Vardaka, Elizabeth; Kountouras, Constantinos; Tzilves, Dimitrios; Kotronis, Georgios; Boutsikou, Efimia; Gialamprinou, Dimitra; Exadaktylos, Aristomenis; Katsinelos, Panagiotis
Abstract : Click here to view the Response from Erőss et al .